Injuries in Collegiate Wrestlers at an Elite Division I NCAA Wrestling Program: An Epidemiological Study - Otero, Jesse E. (Iowa Orthop J, 2017)
BACKGROUND: Injury is common in the sport of wrestling. More than 6000 athletes compete in NCAA wrestling yearly. Despite this popularity, little is known about the epidemiology of wrestlers’ injuries and factors affecting return to competition. We hypothesized that patterns of injury and associated factors influence return to participation. METHODS: Retrospective database review of one Division I NCAA wrestling program over nine seasons (2002 to 2011). RESULTS: From 2002 to 2011, 125 wrestlers were varsity participants at a single NCAA Division I program. Among these wrestlers, there were 4275 exposures per year on average. We identified 1034 musculoskeletal injuries, skin injuries, and concussions in 120 athletes (96% of participants). Eighty-two percent of athletes missed at least one day secondary to these injuries, while 69% were unable to compete in at least one match. The injury rate was estimated at 19.6 (SD 16.5) per 1000 exposures. The rate of injuries requiring surgery was estimated at 1.4 (SD 2.1) per 1000 exposures. Weight class, record, age at injury, and eligibility status did not affect the rate or type of injury. A significant difference was noted in the athletes who returned to competition following surgery. Athletes who returned to competition after surgical treatment for an injury ultimately competed in more matches (62.4 vs 18.2, p < 0.001), had more wins (45.2 vs 12.1, p<0.001) and a higher win percentage (67.5 vs 51.2 p < 0.01) than those who did not return following surgery. CONCLUSION: Return to competition in collegiate wrestling is dependent on many factors in addition to severity of injury and surgery type. There is a positive association between return to sport and success as a collegiate wrestler. Our findings will be helpful to wrestlers and coaches in guiding expectations after injury. Level of Evidence: Level 4 diagnostic